Identifying Trajectories of Maltreatment Revictimization and Juvenile Justice Outcome: A Latent Class Analysis of Subtype, Timing, and Chronicity - Cho, Minhae (Journal of interpersonal violence, 2024)
Continued exposure to abuse or neglect is a strong predictor for immediate and long-term negative developmental outcomes including developmental delays, disabilities, poor school performance, criminal behavior, and mental health issues. The purpose of this study was to identify distinct subgroups of children with repeat victimization based on maltreatment timing, subtype, and chronicity and to examine how the unique subgroups are related to youth’s juvenile justice outcome. Using data from Longitudinal Studies of Child Abuse and Neglect, this study included 286 children (47% males, 41% blacks) with more than one report for substantiated maltreatment from birth to age 17. Latent class analysis was employed to identify heterogeneity in the patterns of maltreatment revictimization. Four latent classes emerged: (a) Prevailing Early Neglect (52.6%); (b) Co-occurring Maltreatments in Preschool Age (20.1%); (c) Incremental Neglect with Sexual Abuse in School Age (18.7%); and (d) Co-occurring Maltreatments in School Age (8.6%). Black children were overrepresented in Incremental Neglect with Sexual Abuse in School Age compared to white and other racial groups of children. Ordinal logistic regression analysis indicated that there was no significant difference in the juvenile justice outcome across four subgroups of children with revictimization. Our person-centered investigations of maltreatment subtype, timing, and chronicity highlight the need for precise assessment and prevention strategies based on a more nuanced understanding of various patterns of childhood maltreatment revictimization.